Study of outcome of patient with faecal fistula - Chaudhari, Nitin; Bariya, Hitesh; Chaudhari, Hina (International Surgery Journal, 2016)
Background: Approximately 80% gastrointestinal fistulas occur following surgery. Due to the high morbidity and mortality associated with gastrointestinal fistula, effective treatment is important. Therefore, this study was conducted to study the outcome of management of patients of gastrointestinal fistula. Methods: 30 Patients developing the condition following surgery were included. All patients were treated either conservatively or operatively by various means and varying period of time. Treatment was focused on the correction of dehydration, controlling sepsis, management of electrolyte imbalance. Results: Younger patients had better fistula healing rate (85%) than older (70%). A high rate of spontaneous healing was observed (85%) in patients who were managed conservatively. Patients with low output fistula had better fistula closure rate as compared to high output fistula. Ileum was the most common site for fistula formation, account for 43.33% of all fistulas. Spontaneous healing rate was better in fistula involving large bowel and duodenal fistula. Patients having both anemia and hypoproteinemia had poor healing rate (72.73%) as compared to those having only anemia and hypoproteinemia. Conclusions: Conservative management with emphasis on improvement of nutrition, control of sepsis, management of fluid and electrolyte balance and control of fistula output supersedes than operative management. Operative intervention must be done in selected cases after improvement of nutritional status and control of infection.